The effect of different forms of dysglycemia during pregnancy on maternal and fetal outcomes in treated women and comparison with large cohort studies - Soliman, Ashraf; Salama, Husam; Al Rifai, Hilal; De Sanctis, Vincenzo; Al-Obaidly, Sawsan; Al Qubasi, Mai; Olukade, Tawa (Acta Biomedica Atenei Parmensis, 2018)
Aims of the study: We describe the impact of different forms of dysglycemia on maternal and neonatal health. This research is a part of the PEARL-Peristat Maternal and newborn registry, funded by Qatar National Research Fund (QNRF) Doha, Qatar. Methods: A population-based retrospective data analysis of 12,255 women with singleton pregnancies screened during the year 2016-2017, of which 3,027 women were identified with gestation diabetes mellitus (GDM) during pregnancy and 233 were diabetic before pregnancy. Data on maternal outcome was collected from the PEARL-Peristat Maternal and newborn registry. Results: The prevalence of GDM and diabetes mellitus (DM) was 24.7 % and 1.9%, respectively. 55% of DM, 38% of GDM and 25.6% of controls were obese (p<0.001). 71% of pregnant women with DM and 57.8% of those with GDM were older than 30 years versus 44.2% of controls. Pregnant women with DM or GDM had higher prevalence of hypertension versus normal controls (9.9%, 5.5% and 3.5%, respectively; p<0.001). Among women with vaginal deliveries, the proportion of women with induction of labor was significantly higher in the DM and GDM compared to control subjects (33.9%, 26.5% and 12.4%, respectively; p<0.001). The number of women who underwent Cesarean section was significantly higher in the DM and GDM groups versus normal controls (51.9%, 36.8%, and 28.5%, respectively; p<0.001). Preterm delivery was significantly higher in women with DM and GDM (13.7% and 9%, respectively versus normal women (6.4%); p<0.001). Babies of DM and GDM had significantly higher occurrence of respiratory distress (RDS) or transient tachypnea (TTS): 9% and 5.8 % versus normal controls (4.8%). Macrosomia was more prevalent in babies of DM (6.4%) and GDM (6.8%) compared to controls (5%) (p: <0.001). Significant hypoglycemic episodes occurred more frequently in babies of DM and GDM women (11.2% and 3%, respectively) versus controls (0.6%) (p: <0.001. Infants of DM and GDM mothers required more treatments of phototherapy (9.4% and 8.9%, respectively) versus those born to normal women (7.2%) (p: 0.006). The prevalence of congenital anomalies and neonatal death did not differ between the groups. Conclusions: Despite the improvement in the prenatal diagnosis and management of dysglycemia, there is still a higher prevalence of prematurity, macrosomia, and hypoglycemia in infants of mothers with DM and GDM. Measurements to reduce obesity and control dysglycemia in women during the childbearing period are highly required to prevent the still higher morbidity during pregnancy.